Changing the course of comorbid eating disorders and depression: what is the role of public health interventions in targeting shared risk factors? - Becker, Carolyn Black (BioMed Central, 2014)
Public health has a productive history of improving global health due to its focus on reaching large populations using effective and scalable interventions. Yet, the marriage between evidence-based science and the implementation of community/public health interventions within mental illness remains underdeveloped. Research suggests that major depression is the most commonly cited comorbidity for eating disorders (EDs). Thus, identification of public health strategies that jointly impact depression and EDs, including shared risk factors, has the potential to significantly impact mental health suffering. The primary aim of this paper is to examine and discuss such public health approaches as well as explore cues taken from public health efforts to inform future directions in research and clinical practice. As a comprehensive review of all public health initiatives that address EDs and depression is beyond the scope of this paper, this paper reviews a series of programs/approaches that either are of large scale and/or have received empirical support. In particular, public health related interventions that aim to reduce variable risk factors associated with EDs and depression, as well as interventions that aim to reduce continuous measures of ED and depression symptoms are reviewed. To date, despite significant progress in modifying risk factors for EDs and depression, the field still lacks a public health study that has been appropriately designed and/or adequately powered to assess true ED/depression prevention effects. Further, although several programs show promise, many widely disseminated approaches lack empirical support, raising concerns about the potential for waste of limited resources. In summary, although the combination of prevention and public health based approaches appear to have merit when trying to move the needle on risk factors and symptoms associated with EDs and/or depression, further research is needed to investigate the reach and effectiveness of large scale dissemination efforts of such endeavors.